Comparative Screening of Private, Public, and Bottled Drinking Water In Vitro Bioactivity - Paul M. Bradley; Kristin M. Romanok; Kelly L. Smalling; Stephanie E. Gordon; Sergei S. Makarov; Alexander V. Medvedev; Molly L. Schreiner (ACS ES&T Water, 2026)
Abstract This study compares in vitro bioactivity profiles of extracts from private tapwater (51 samples), public tapwater (143 samples), and bottled water (31 samples), using high-throughput, multiplex, transcription factor screening. Of 48 biological end points tested, 25 showed significant (≥50% above the field blank) activity. Frequently detected (≥10% of samples) bioactivities (in decreasing order) included xenobiotic metabolism (pregnane X receptor [PXR], aryl hydrocarbon receptor [AhR]), antioxidant response (antioxidant response element-binding nuclear factor erythroid 2-related factor 2 [NRF2], activator protein 1 [AP-1]), endocrine signaling (estrogen receptor [ER], peroxisome proliferator-activated receptor [PPAR]), and metals response (metals response element [MRE]). Significant bioactivities were observed across all drinking water supplies, with some statistical differences identified. Bioactivities were moderately to strongly correlated with several individual exposure and corresponding benchmark- or activity-weighted metrics, particularly for disinfection byproducts. Significant (α = 0.05) but weak correlations between measured bioactivity resemblance patterns and those of the inorganic–organic exposure, toxicity-quotient (TQ), and exposure-activity-ratio (EAR) resemblance matrices suggest that key drivers of observed drinking water bioactivity were not captured by the extensive, targeted exposure assessment. Results highlight the need for effects-based monitoring combined with improved exposure analysis to better assess health risks from low-level contaminant mixtures in drinking water.